Paediatric asthma education: Implementation of video‐based education for families. (17th January 2022) - Frydenberg, Alexis; Oborne, Naomi; Polley, Clare; Littlejohn, Emily; Gray, Amy
Abstract : Aim: To understand the impact of an asthma education video resource introduced to the short stay unit (SSU) of a tertiary paediatric hospital on: (i) parental understanding of and confidence in managing their child's asthma; (ii) the impact of this resource on nurse‐led education practices; and (iii) readmission rates. Methods: A mixed methods study was conducted in the SSU over an 18‐month period using quantitative survey data from parents and nursing staff and qualitative data from nursing staff focus groups. Results: Of 117 parents surveyed, 94% reported an increase in their understanding of asthma. Following the introduction of the resource, there were fewer nurse‐led education sessions delivered (1.91 vs. 1.54, P  = 0.04) and a trend towards reduction in time spent delivering this education (27.24 vs. 24.98 min, P  = 0.47). Nursing staff confidence in the family's understanding of asthma education was similar pre‐ and post‐implementation (4.22 vs. 4.30, P  = 0.97). Readmission rates dropped by 25% (readmissions within 1 month) and by 33.3% (readmission within a week) in the post‐intervention cohort. Conclusions: Our asthma education video resource was demonstrated to be an acceptable and effective way of delivering asthma education to families. It created efficiency and consistency for nursing education and practice in our SSU. This resource was viewed by nursing staff as a useful adjunct to their education, enabling consistent messaging and helping structure education delivery. It has been incorporated into hospital systems and national resources which we hope will translate to a reduction in burden of asthma across the community.